Can Smartphones be used as an information delivery tool in post-conflict context? - Jimale, Abdikadir (2020)
In areas where reaching out to rural farmers is difficult, Information and Communication Technologies (ICTs), such as mobile smartphones may offer an opportunity to share timely information on weather, markets, farm inputs, and research results to the farmers. Access to this type of information could potentially enhance farmers' farm productivity and their ability to make crucial decisions related to farm management in the face of climate variability. Mobile technologies have been identified as one way of easing information communication with farmers, especially in remote hard to reach areas. As in most African counties, the mobile technology sector is the leader in ICT development in Somalia, with approximately 7 out of 10 Somalis using mobile money services regularly. This creates and provides an opportunity for communicating and delivering information to farmers using ICTs technologies. What is not well understood is how ICTs, particularly smartphones, could be used as an information communication tool in post-conflict areas like rural Somalia. This study set out to assess the feasibility of using smartphones as a tool for delivering agricultural advisory information to rural farmers in the Afgooye district of Somalia. During a period of 11 weeks between December 2018 to March 2019, interviews were conducted with 30 vegetable growers and ten key informants. Individual interviews were carried out with the key-informants, while semi-structured questionnaire interviews were conducted with the farmers. The findings of the study revealed that the necessary enabling conditions for the adoption and implementation of the smartphone-based advisory system in the study area exist. Moreover, the use of smartphones among surveyed vegetable growers was influenced by factors like age, literacy level, and non-farm income source. Growers that had land title deeds, as well as non-farm income, were more likely to own a smartphone or to buy one compared with other farmers who rented land or shared their farmland. Furthermore, human security issues, as well as internet connectivity, were the main factors that constrain the access and use of smartphones in the Afgooye area. Mobile data cost was another factor stated by the farmers as restricting the optimal use of smartphones. The main conclusion of this study is that while there is a potential of using smartphones in the study area as an information delivery tool, there are both internal and external challenges that need to be improved. Specifically, many of the farmers identified security and credible information source providers as more urgent issues. Somalia is in the process of post-conflict construction, therefore, peace and security continues to be threatened by a range of external forces.